The Influence of Promotion, Brand Image, and Service Quality on Purchasing Decisions on the Bukalapak Site Through Purchase Interest as an Intervening Variable: The Influence of Promotion, Brand Image, and Service Quality on Purchasing Decisions on the Bukalapak Site Through Purchase Interest as an Intervening Variable - Rusmawati, Nadilla Putri; Prabowo, Heri; Sijabat, Rauly (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
One of the developments in business on the internet is electronic commerce or what is commonly known as e-commerce. Ecommerce is a trading process (purchasing, selling, exchanging products, services, or information) carried out via computers or other devices that are usually connected to the internet. There are many e-commerce sites that already exist in Indonesia, such as Shopee, Tokopedia, Bukalapak and others. With the large number of e-commerce sites emerging in Indonesia, competition for online buying and selling businesses through e-commerce is getting tighter. This intense competition will cause e-commerce to experience a decline in sales, one of which is Bukalapak e-commerce. Based on this, this research aims to analyze the influence of promotion, brand image and service quality on purchasing decisions with purchase interest as an intervening variable in Bukalapak e-commerce. The research method uses quantitative research. The population in this study were undergraduate students at PGRI University Semarang who used or knew about Bukalapak e-commerce. The sample in this study was 97 respondents. The technique used in collecting data is by observing and distributing questionnaires. The data processing technique uses the SmartPLS application based on this research, the research results show that Promotion has an effect on increasing purchasing decisions with a P - Value of (0.024), brand image has no positive and significant effect on purchasing decisions with a P -Value of (0.300), service quality has a positive and significant effect on purchasing decisions with a P - Value of (0.000 ), promotion has no positive and significant effect on purchase interest with a P-Value of (0.268), brand image has a positive and significant effect on purchase interest with a P-Value of (0.001), service quality has a positive and significant effect on purchase interest with P- Value is (0.002), promotion has no positive and significant effect on purchasing decisions through purchase interest with a P-Value of (0.268), brand image has a positive and significant effect on purchase decisions through purchase interest with a P-Value of (0.004), and quality service has a positive and significant effect on purchasing decisions through purchase interest with a P-Value of (0.022).